Forecasting in Austrian companies: Do small and large Austrian companies differ in their forecasting processes?. Issue 3 (9th November 2015) - Hofer, Peter; Eisl, Christoph; Mayr, Albert
Abstract : Purpose: – The purpose of this paper is a comparison of forecasting behaviour of small and large Austrian firms, analysing their forecast practices in a volatile business environment. Design/methodology/approach: – The empirical analysis of the paper, deductive by nature, was conducted by means of a quantitative online-survey (199 data sets). The relationship of perceived volatility and forecast predictability was evaluated by correlation analysis. t -Test and analysis of variances were used to examine significant differences in the forecast characteristics between small and large Austrian companies and different industries. Findings: – The study provides evidence that the surveyed companies have been hit by volatility, showing that Austrian SMEs are significantly more severely affected than large companies. The increasing volatility correlates with a reduced forecast predictability of sales quantities and commodity prices. Large Austrian companies primarily use a broad spectrum of qualitative forecasting methods. In contrast, Austrian SMEs utilize simple quantitative and qualitative forecast techniques, like the forward projection of historical data. Research limitations/implications: – Relevant for the forecasting of small and large companies. Practical implications: – Although management requests a broad spectrum of forecast qualities, the current usage of less sophisticated methods reveals a gap between intention and reality. Companies that supplement their qualitative techniques by sophisticated quantitative ones should expect less forecast bias. Originality/value: – This paper initially compares forecast methods in large and small Austrian firms and additionally provides the impact of volatility on the forecast predictability.